2012
DOI: 10.1021/ic301391s
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Tripodal Ligand Containing Three N-Heterocyclic Donor Functions and Its Copper Complexes: Crystallization of [LCuI]22+/[L2CuII]2+ Stereoisomers and Tyrosinase Activity

Abstract: A novel chiral ligand system L containing one pyridyl and two imidazolyl donor functions has been synthesized and investigated with respect to its Cu(I) and Cu(II) coordination chemistry. Reaction with [Cu(MeCN)4]PF6 and [Cu(MeCN)4]OTf led to the dimeric complexes [LCu]2X2 (1, X = PF6; 2, X = OTf) with the ligands L in different configurations (R,S). The ligand matrix formed in these complexes can also host a Cu(II) ion instead of two Cu(I) ions so that mixed crystals of [L2Cu]X2 and [LCu]2X2 can be produced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Karlin and co‐workers followed in 2009 with an imidazolyl‐containing tris(2‐pyridylmethyl)amine (TMPA) derivative,40 and in 2012 Limberg et al. presented a tripodal ligand containing sterically demanding imidazolyl moieties for the stabilisation of Cu I and Cu II species 41. Those species were also capable of oxygen activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karlin and co‐workers followed in 2009 with an imidazolyl‐containing tris(2‐pyridylmethyl)amine (TMPA) derivative,40 and in 2012 Limberg et al. presented a tripodal ligand containing sterically demanding imidazolyl moieties for the stabilisation of Cu I and Cu II species 41. Those species were also capable of oxygen activation.…”
Section: Introductionmentioning
confidence: 99%
“…presented at ripodal ligand containing sterically demanding imidazolyl moieties for the stabilisation of Cu I and Cu II species. [41] Those species werea lso capable of oxygen activation. Earliert his year,t hey demonstrated the hydroxylationo f2 ,4-ditert-butylphenol( DTBP)t ot he corresponding quinonew itht his system.…”
Section: Introductionmentioning
confidence: 99%
“…There has been continuous interest in the coordination chemistry of copper complexes, and much attention has been paid to the design and synthesis of Cu(I) and Cu(II) complexes [1][2][3][4][5]. These complexes have been widely used in metal organic framework materials (MOFs), luminescent materials, magnetic materials, and efficient catalysts [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the binding motif P was found to be relevant to biological dioxygen fixation/activation in proteins such as the abovementioned hemocyanin or the monooxygenase tyrosinase , . Moreover, studies on bioinorganic model compounds indicated that factors such as electronic and steric properties of the ligand environment, temperature,, solvent,, concentration,, and the nature of the counterion[13a], [16a], , may have a strong impact on the equilibrium position between P and O , . Having synthesized different dicopper(I) complexes of our new ligands, it was thus of interest to explore their O 2 reactivity.…”
Section: Introductionmentioning
confidence: 99%